Overcoming the barriers to umbilical cord blood transplantation - KELLY, SUSAN STABA (Cytotherapy, 2010)
Umbilical cord blood (UCB) transplantation (UCBT) has seen a marked increase in utilization in recent years, especially in the pediatric population; however, graft failure, delayed engraftment and profound delay in immune reconstitution leads to significant morbidity and mortality in adults. The lack of cells available for post-transplant therapies, such as donor lymphocyte infusions, has also been considered a disadvantage. To overcome the cell–dose barrier, the combination of two UCB units is becoming commonplace in adolescent and adult populations, and is currently being studied in pediatrics as well. In some studies, the use of two UCB units appears to have a positive impact on outcomes; however, engraftment is still suboptimal. A possible additional way to improve outcome and extend applicability of UCBT is via ex vivo expansion. Studies to develop optimal expansion conditions are still in the exploratory phase; however, recent studies suggest expanded UCB is safe and can improve outcomes. The ability to transplant across HLA disparities, rapid procurement time and decreased graft-versus-host disease (GvHD) seen with UCBT makes it a promising stem cell source and, while barriers exist, consistent progress is being made to overcome them.